Inhibition of recombinant aldose-6-phosphate reductase from peach leaves by hexose-phosphates, inorganic phosphate and oxidants - Hartman, Matias Daniel (2017)
Glucitol, also known as sorbitol, is a major photosynthetic product in plants from the Rosaceae family. This sugar alcohol is synthesized from glucose-6-phosphate by the combined activities of aldose-6-phosphate reductase (Ald6PRase) and glucitol-6-phosphatase. In this work we show the purification and characterization of recombinant Ald6PRase from peach leaves. The recombinant enzyme was inhibited by glucose-1-phosphate, fructose-6-phosphate, fructose-1,6-bisphosphate and orthophosphate. Oxidizing agents irreversibly inhibited the enzyme and produced protein precipitation. Enzyme thiolation with oxidized glutathione protected the enzyme from insolubilization caused by diamide, while incubation with NADP+ (one of the substrates) completely prevented enzyme precipitation. Our results suggest that Ald6PRase is finely regulated to control carbon partitioning in peach leaves.